Embryo Cleavage - Wu, Bin (IntechOpen, 2017)
Embryo cleavage experiences a series of critical events and remarkable epigenetic modifications, especially morphological change and gene expression. The development of current assisted reproductive technology has created some new observations and novel discoveries in cleavage embryos. This book updates some new technologies and methods on the study of cleavage embryos to select high-quality embryos for transfer and improve embryo implantation and pregnancy. Major contents include embryo cleavage morphokinetics based on time-lapse imaging, gene expression of cleavage embryo and noninvasive assessment, and improving embryo cleavage technology. Thus, this book will greatly add new information for embryologists to select good-quality embryos for transfer to improve human embryo transfer pregnancy rate.